The diagnosis and treatment of minimal hepatic encephalopathy - Zhan, Tianzuo; Stremmel, Wolfgang (Deutsches Ärzteblatt, 2012)
Hepatic encephalopathy (HE) is a potentially reversible, metabolically caused disturbance of central nervous system function that occurs in patients with acute or chronic liver disease. It encompasses a broad spectrum of neurological symptoms of...